Precision airflow optimization in air-assisted orchard sprayers to reduce drift and improve coverage: Design and Performance Analysis of an Optimized Airflow System - İtmeç, Medet (International Journal of Agricultural and Biological Engineering, 2026)
The effectiveness of air-assisted orchard spraying depends on matching airflow to canopy structure, since improper airflow reduces coverage and increases spray drift. However, the optimal airflow conditions that balance coverage and drift remain unclear. A hydraulically driven axial-fan orchard sprayer capable of continuously adjusting airflow was developed, and different airflow levels were generated by regulating fan speed through a proportional valve operated at different voltage levels. Air velocities generated at different voltage levels were first quantified under laboratory conditions and subsequently validated in a pecan orchard by measuring canopy-exit air velocity under airflow-only conditions. Finally, spray applications were performed at a constant application volume while varying air velocity, and coverage and drift (ground and airborne) were evaluated using water-sensitive papers (WSP). At 4.50 V (air velocity: 21 m/s), the spray index (Io) was close to zero and positive, indicating the optimal operating condition. Under these conditions, coverage reached 35.94% on water-sensitive papers in the middle canopy. Furthermore, ground drift was 18.15% at the closest point to the tree, whereas airborne drift was 13.58% at a height of 3 m. Appropriate adjustment of airflow directed to the canopy improved leaf surface coverage while reducing both ground and airborne spray drift. At the operating condition that resulted in the lowest overall drift and the most effective spray coverage (4.5 V, 460 r/min), fuel consumption decreased to 6.24 L/h, compared with 7.76 L/h under the conventional operating condition (5.0 V, 540 r/min). This study provides a practical methodology for determining airflow levels that balance spray coverage, drift reduction, and fuel consumption in orchard spraying applications. Key words: airflow configuration; orchard sprayer; drift; canopy density DOI: 10.25165/j.ijabe.20261904.10629 Citation: İtmeç M. Precision airflow optimization in air-assisted orchard sprayers to reduce drift and improve coverage. Int JAgric & Biol Eng, 2026; 19(4): 34–42.